IoT Applications help people with Autism - Fotoglou, Anestis; Moraiti, Ioanna; Dona, Katerina; Katsimperi, Alexandra; Tsionakas, Konstantinos; Karabatzaki, Zoi; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
This article is aimed at teachers, parents, caregivers, and everyone interested in special education and the autism spectrum. The purpose is to present the usefulness of technological applications in special education and specifically refers to the usefulness of Internet of Things applications in Autism disorder. Digital technologies have come actively into everyday life to provide solutions even in a complex fields such as special education. Technology and the internet of things promise to people who belong to the autism spectrum but also to their parents’ solutions that aim at their integration into society. Smart devices save time, data, and several treatments. The Autism Spectrum Disorder, the IoT technology in the field of Medicine - IoT, the IoT applications with the help of artificial intelligence, and the skills acquired by people with autism because of these technological innovations are some of the fields that will be analyzed.